Optimal cost reimbursement of health insurers to reduce risk selection - Mathias Kifmann; Normann Lorenz (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2005)
In the absence of a perfect risk adjustment scheme, reimbursing health insurers' costs can reduce risk selection in community-rated health insurance markets. In this paper, we develop a model in which insurers determine the cost efficiency of health care and have incentives for risk selection. We derive the optimal cost reimbursement function which balances the incentives for cost efficiency and risk selection. For health cost data from a Swiss health insurer, we find that an optimal cost reimbursement scheme should reimburse costs only up to a limit.
urn:nbn:de:bsz:352-opus-14306
Keywords: H42; I18; 330; health insurance; risk selection; risk adjustment; Krankenversicherung; Gesetzliche Krankenversicherung; Rückvergütung; Gesundheitskosten; Adverse Selection; Schweiz